Amino acids in hematologic malignancies: Current status and future perspective - Wang, Mengyao; Zhao, Ailin; Li, Meng; Niu, Ting (Frontiers in Nutrition, 2023)
In recent years, growing emphasis has been placed on amino acids and their role in hematologic malignancies. Cancer cell metabolism is altered during tumorigenesis and development to meet expanding energetic and biosynthetic demands. Amino acids not only act as energy-supplying substances, but also play a vital role via regulating key signaling pathways, modulating epigenetic factors and remodeling tumor microenvironment. Targeting amino acids may be an effective therapeutic approach to address the current therapeutic challenges. Here, we provide an updated overview of mechanisms by which amino acids facilitate tumor development and therapy resistance. We also summarize novel therapies targeting amino acids, focusing on recent advances in basic research and their potential clinical implications.